When CMRP met alkyl vinyl ketone: visible light induced living radical polymerization (LRP) of ethyl vinyl ketone (EVK). Issue 81 (20th September 2016) - Zhao, Yaguang; Liu, Xu; Liu, Yuchu; Wu, Zhenqiang; Zhao, Xianyuan; Fu, Xuefeng
Abstract : Photo responsive polyethyl vinyl ketone (PEVK) and various block copolymers were prepared through the visible light induced cobalt mediated radical polymerization (CMRP) process. Abstract : Photo responsive polyethyl vinyl ketone (PEVK) and various block copolymers were prepared through the visible light induced cobalt mediated radical polymerization (CMRP) process. The first order kinetics and linear increase in molecular weight with conversion demonstrated a well-behaved system. Chain extension experiments showed the retention of the living end of PEVK.